Totalitarian dictatorship and autocracy - Friedrich, Carl J. (Harvard University Press, 1956)
An effort, as the authors put it, "to delineate, on the basis of fairly generally known and acknowledged factual data, the general model of totalitarian dictatorship and of the society which it has created." Six basic features are discerned: an ideology, a single party, a terroristic police, a communications monopoly, a weapons monopoly and a centrally directed economy.